Initial impact of a national programme to contain the spread of carbapenemase-producing Enterobacterales in Ireland. (March 2021) - Vellinga, A.; Brennan, W.; Humphreys, H.; Burns, K.
Summary: Background: Carbapenemase-producing Enterobacterales (CPE) are an emerging cause of healthcare-associated infection (HCAI). In October 2017, a National Public Health Emergency on CPE was declared in Ireland, leading to improved CPE surveillance, implementation of performance monitoring and reporting, and a CPE national expert advisory group. Aim: To evaluate the impact of measures taken to control CPE. Methods: From August 2017, all acute Health Service Executive (HSE) hospitals were required to report performance indicators related to CPE control (number of CPE tests and number of newly detected CPE). The number of screening samples increased due to this requirement. Monthly incidences were calculated using the overall number of bed-days used (BDU) per hospital. All newly detected CPE were submitted for further genetic identification. Data analysis and predictions were performed for two separate periods (first year and second year after measure implementation). Findings: Over the two-year period studied, the average incidence of CPE cases per 10, 000 BDU increased from 1.3 (±0.5) for year 1 to 1.7 (±0.4) for year 2, while the incidence of CPE cases per 1000 screens fell from 3.2 (±0.7) in year 1 to 2.3 (±0.6) in year 2. The OXA-48 gene was most often detected (72%), followed by KPC (13%) and NDM (7%). Conclusion: The declaration of the National Public Health Emergency to enhance prevention and control measures for CPE in Ireland is a unique approach in the EU/EEA. Our preliminary results suggest a positive effect on controlling the incidence of CPE in the acute HSE hospital system in Ireland.